Physical Self Matters: How the Dual Nature of Body Image Influences Smart Watch Purchase Intention - Wang, Teng; Sun, Yongqiang; Liao, Shengwu (Frontiers in Psychology, 2022)
To determine the role of physical self in body-involving consumption, we explore how body image influences purchasing intention toward hybrid products with body-involving features. In this study, we establish the dual nature of body image: specifically, body image influences intention to purchase via the perception of utilitarian value and symbolic value. Further, we find a competitive mediation in which positive body image negatively influences purchase intention (direct effect), while positive body image is positively related to purchase intention via utilitarian and symbolic value (indirect effect). This indicates that without the mediation testing of the utilitarian-symbolic framework, the positive influence of body image will be “hidden”. Additionally, the mediated effect of symbolic value is moderated by personal innovativeness toward technology, suggesting that a consumer’s knowledge of wearables enhances the effect of body image. With the introduction of body image, this paper provides a more comprehensive model to analyze purchase intention with regard to digital products with body-involving features.